Eculizumab application during pregnancy in a patient with paroxysmal nocturnal hemoglobinuria: A case report with review of the literature. Issue 8 (27th June 2018) - Lauritsch‐Hernandez, Lisa Sophie; Kraehenmann, Franziska; Balabanov, Stefan; Kimmich, Nina
Key Clinical Message: Eculizumab is highly effective in inhibiting complement activation and has successfully shown to prevent complications and to improve quality of life in patients with paroxysmal nocturnal hemoglobinuria (PNH). Its application during pregnancy showed favorable fetal and maternal outcome in the presented case and has proven to be effective without raising safety concerns. Abstract : Eculizumab is highly effective in inhibiting complement activation and has successfully shown to prevent complications and to improve quality of life in patients with paroxysmal nocturnal hemoglobinuria (PNH). Its application during pregnancy showed favorable fetal and maternal outcome in the presented case and has proven to be effective without raising safety concerns.